UK Degree Apprenticeships a Year in Review - Goodyer JE (My University, 2023)
This report summarises the first year operation of the digital & technology solutions degree apprenticeship at Manchester Metropolitan University (MMU) in the UK. It focuses on MMU's progress and their SME engagement. This report provides valuable insights, adding detail and depth, to the understanding of the early stages of the Trailblazer journey.